2019
DOI: 10.1016/j.stemcr.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Mesoderm and Neural Crest-Derived Pericytes from Human Pluripotent Stem Cells to Study Blood-Brain Barrier Interactions

Abstract: Summary In the CNS, perivascular cells (“pericytes”) associate with endothelial cells to mediate the formation of tight junctions essential to the function of the blood-brain barrier (BBB). The BBB protects the CNS by regulating the flow of nutrients and toxins into and out of the brain. BBB dysfunction has been implicated in the progression of Alzheimer's disease (AD), but the role of pericytes in BBB dysfunction in AD is not well understood. In the developing embryo, CNS pericytes originate from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(110 citation statements)
references
References 30 publications
4
106
0
Order By: Relevance
“…Differentiation of iPSCs into pericytes was carried out as described previously 55 . Briefly, iPSCs were dissociated with ReLeSR (catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…Differentiation of iPSCs into pericytes was carried out as described previously 55 . Briefly, iPSCs were dissociated with ReLeSR (catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…Easy accessibility of pericytes for autologous transplantation highlights their capabilities for future therapeutic studies (Geranmayeh et al, 2019). Since pericyte-like cells derived from induced pluripotent stem cells (iPSC) acquire BBB properties and are incorporated with iPSC-derived endothelial cells, astrocytes and neurons (Faal et al, 2019;Stebbins et al, 2019), iPSC-derived pericytes might also be promising for implantation therapy of AD and other neurological disorders. Pericytes themselves have been shown to acquire stem cell-like and microglial properties after ischemia (Özen et al, 2014;Nakagomi et al, 2015a), which offers another potential therapeutic target for recovery form CNS diseases.…”
Section: Implantation Therapy Application Of Multipotential Stem Celmentioning
confidence: 99%
“…Previous studies demonstrated that pericytes and smooth muscle cells in all blood vessels of the face and forebrain are derived from the cephalic (cranial) neural crest 15,16 . Most recently, two studies also verified that forebrain pericyte-like cells (PCs) could be readily differentiated from human pluripotent stem cells (hPSCs) through the cranial neural crest (CNC) stage 17,18 . However, the in vivo functional characteristics and therapeutic potential of hPSC-derived pericyte-like cells still need to be clarified.…”
mentioning
confidence: 97%